2007
DOI: 10.1101/lm.504107
|View full text |Cite
|
Sign up to set email alerts
|

Effects of paradigm and inter-stimulus interval on age differences in eyeblink classical conditioning in rabbits

Abstract: The aim of this study was to examine parameters affecting age differences in eyeblink classical conditioning in a large sample of young and middle-aged rabbits. A total of 122 rabbits of mean ages of 4 or 26 mo were tested at inter-stimulus intervals (ISIs) of 600 or 750 msec in the delay or trace paradigms. Paradigm affected both age groups dramatically, with superior performance in the delay paradigm. ISI was salient as middle-aged rabbits were significantly impaired in 750-msec compared with 600-msec delays… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
16
0

Year Published

2009
2009
2015
2015

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 63 publications
0
16
0
Order By: Relevance
“…Previous work in our laboratory with the 750 ms ISI in New Zealand white rabbits (Woodruff-Pak et al, 2007) and the 500 ms ISI in C57BL/6 mice (Spath and Woodruff-Pak, 2004) indicated that when ISIs are matched in the trace and delay paradigms, acquisition in trace is slower and reaches a lower asymptote. ISI-matched delay and trace eyeblink conditioning tasks differentially engage forebrain circuitry associated with higher-order learning and memory paradigms (Moyer et al, 1990; Ivkovich and Stanton, 2001; Green and Arenos, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…Previous work in our laboratory with the 750 ms ISI in New Zealand white rabbits (Woodruff-Pak et al, 2007) and the 500 ms ISI in C57BL/6 mice (Spath and Woodruff-Pak, 2004) indicated that when ISIs are matched in the trace and delay paradigms, acquisition in trace is slower and reaches a lower asymptote. ISI-matched delay and trace eyeblink conditioning tasks differentially engage forebrain circuitry associated with higher-order learning and memory paradigms (Moyer et al, 1990; Ivkovich and Stanton, 2001; Green and Arenos, 2007).…”
Section: Introductionmentioning
confidence: 87%
“…We have also demonstrated that, in addition to increasing Aβ, cholesterol-enriched diets increase tau phosphorylation and oxidative stress in rabbits (Ghribi et al, 2006 a,b). Additionally, the eye blink classical conditioning that is impaired in AD patients is also impaired in the rabbit model (Woodruff-Pak et al, 2007. Schreurs et al, 2012).…”
Section: Introductionmentioning
confidence: 99%
“…Many animals, ranging from worms to humans, show a decline in cognitive function with increasing chronological age (Marriott and Abelson, 1980;Grotewiel et al, 2005;Mell et al, 2005;Murakami and Murakami, 2005;Yu et al, 2006;Soei and Daum, 2008;Woodruff-Pak et al, 2008). In contrast to most animal species, honeybees normally show a strong relationship between chronological age and social role.…”
Section: Introductionmentioning
confidence: 99%